2022
DOI: 10.1002/cche.10589
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the functionality of faba bean protein isolates with major legume proteins in the market

Abstract: Background and Objectives The production of faba beans (Vicia Faba L.) is emerging in the Canadian prairies. To investigate their utilization potential as value‐added ingredients, the physicochemical and functional properties of protein isolates prepared from three faba bean cultivars (Fabelle, Malik, and Snowbird) currently grown in Canada were compared with those of yellow pea (CDC Amarillo) and soybean (AAC 26‐15). Findings Higher than pea (23.1%), the faba bean had protein contents of ~31.4% and a small am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…Additionally, according to [ 24 ], protein isolates obtained via AE-IP showed a greater surface charge than those made using salt extraction. In agreement with Shi & Nickerson [ 22 ], the high surface charges of the examined legume protein isolates generally suggested excellent solubility in solution at pH 7.
Fig.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, according to [ 24 ], protein isolates obtained via AE-IP showed a greater surface charge than those made using salt extraction. In agreement with Shi & Nickerson [ 22 ], the high surface charges of the examined legume protein isolates generally suggested excellent solubility in solution at pH 7.
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…They discovered that all isolates had statistically identical values for CPI, FPI, LPI, and SPI, respectively, at −47.7, −46.4, −47.2, and − 44.3 mV, which are analogously in line with our findings. Meanwhile, Shi & Nickerson’s [ 22 ] FPI findings was comparable to ours (−41.8 mV), however, at pH 7, SPI in their investigation was shown to be less negative (−38.4 mV) than in our study [ 22 ]. Protein surface charge measurements are influenced by solvent conditions and surface electrochemical properties [ 23 ].…”
Section: Resultssupporting
confidence: 76%
“…Moreover, FB protein has functionalities comparable with soy protein, the most widely used plant‐based protein 12 . Shi 13 reported that water‐holding capacity (WHC) of FB protein isolate (FBPI) from the cultivars Malik and Snowbird were higher than those of soy protein isolate (SPI). FB proteins are non‐allergic and non‐genetically modified, unlike soybean 14 .…”
Section: Introductionmentioning
confidence: 99%